Implementasi Keperawatan Komunitas dalam Upaya Promotif dan Preventif di Wilayah RW 10 Kelurahan Gebang Raya - Safitri, Alfika; Prastiwi, Nurmalyta Dwi; Nurrahmawati; Adiyansyah, Indra; Kamillah, Aulia Hayatul; Rahmadani, Awaliyah; Oktaviani, Bella Eka; Masfufah, Dian Siti; Cahyaseno, Dwi Putri; Ervina; Mutmaisah, Iis (Yayasan Inspirasi El Burhani, 2025)
Introduction: Community health nursing is a professional nursing service that targets individuals and high-risk groups in a comprehensive manner, covering biological, psychological, social, and spiritual dimensions. Its primary focus is to improve the health status of the community through promotive and preventive actions, while still considering curative and rehabilitative aspects. This service is carried out by actively involving the community as partners in identifying and addressing health problems occurring within their environment. Objective: To describe the implementation of community health nursing care carried out in Villa Tangerang Indah, RW 10, Gebang Raya Subdistrict, Periuk District, Tangerang City, Banten Province. Method: The data collection process was carried out through the distribution of questionnaires, direct interviews, and field observations. Once the data were collected, the information was classified based on the number of households recorded in RW 10, Gebang Raya Subdistrict, Periuk District, Tangerang City. Result: Based on the assessment results, it was found that the most prevalent diseases in the area included hypertension (26.7%), diabetes mellitus (20%), gastritis (18.7%), high cholesterol (6.7%), and uric acid (5.3%). Additionally, 22.6% of the population were found to suffer from various other types of illnesses.